Stolen innocence? Observance of the EU Directive on presumption of innocence by Spanish crime reporting (Communication & Society, 2021)
This paper examines the compliance of Spanish crime reporting with the principles of the 2016 EU Directive on presumption of innocence, which aims at preventing the publication of information that might bias the public and the jurors against the suspect. A content analysis applied to a sample of 200 crime news stories published by eleven of the most popular print and online news platforms in 2018 reveals that the Spanish press coverage of crime is centered around the pre-trial and sentence stages, with little attention to the oral trial. The full name and the face portrait of the suspect appear in roughly one-third of the stories, but this overwhelmingly happens in news stories reporting on the court’s decision, so that the presumption of innocence is generally protected. Interestingly, the legacy media are more likely to report on the victim’s full name and the crime details that online digital media. One-fourth of the stories include accusations of guilt, as prosecutor attorneys and other officials are more frequently cited than defense lawyers. Although the Spanish press is largely compliant with the recommendations of the EU Directive, the lack of attention to the oral phase, where the arguments of both parts are deployed and contrasted, leads to a bias in the coverage against the suspect.